(untitled) (Journal of Scientific Research, 2014)
This study was conducted to assess and compare the cardiovascular risk and to explore the demography of CV risk of nonselective cyclooxygenase inhibitors (COX-Is) and selective COX-2-Is in arthritic patients. In this comparative matched case control study adult arthritic patients of either sex taking COX-Is for >1 yr; were included. Arthritic age and sex matched individuals with no history of COX-Is treatment were the controls. Patients those with history of any other disease (e.g. diabetes, hypertension, stroke, IHD etc.) were excluded. Patients were grouped into Control, nonselective COX-I and selective COX-2-I groups. The CV risk factors like blood pressure, blood sugar level(BSL), lipid profile, BMI(body mass index) etc. were assessed and compared; demography of CV risk factors i.e. age, sex, smoking, alcohol, heredity was also studied. Qualitative data was analyzed using Chi-square and quantitative data was analyzed by studentst-test. Study clearly revealed that all NSAIDs exhibit significant CV risk when taken over a period of time as in arthritis. However selective COX 2-Is found to exhibit more CV risk in this regard. Odds ratio (OR) for CV risk=10.3(95% CI: 1.45, 3.31) and OR for CV risk=5.2(95%CI: 1.05, 2.57) for nonselective COX-Is. BMI, BSL and lipid profile; the potential CV risk factors, showed significant impairment in selective COX 2-Is group; P<0.05, P<0.05 and P<0.01 (HDL), P<0.001 (cholesterol), respectively compared to controls and P<0.05 compared to nonselective COX-Is. This study portrays the potential CV risk of selective COX 2-Is and confirms and re-evaluate the results of earlier studies in this regard. Keywords: Anti-arthritic agents; BMI; COX-Is; CV risk; Lipid profile. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17039 J. Sci. Res. 6 (2), 328-338 (2014)